Clinical Presentation and Surgical Outcome of Parotid Gland Tumors- Experience in ENT Department of Rajshahi Medical College Hospital (TAJ: Journal of Teachers Association, 2019)
Objective: To assess the clinical presentation and outcome of surgical treatment of various parotid gland diseases requiring parotidectomy. Setting & design: this was a retrospective study conducted of all patients who underwent different types of parotidectomy in the Department of ENT of Rajshahi Medical College Hospital between January, 2014 to December, 2017.Materials & Methods: Patients presenting with parotid gland disorders requiring various range of parotidectomy admitted in ENT dept. RMCH were included in this study. The location of the tumor and diagnosis was confirmed in every case by advising ultrasound of the parotid region and/or computed tomography scan/MRI along with fine needle aspiration cytology of the swelling. Data regarding age, gender & histology, operative procedure and post-operative complications were meticulously entered in a previously prepared questionnaire for this purpose. Patients were followed up for about two years.Results: Out of 68 patients, 37 (54.4 %) were male and 31 (45.6 %) were female with age ranging from 26 to 63 yrs. with a mean age of 39.5 years. All of them presented with painless parotid lump. 55 Fifty Five Patients (80.9%) had benign pathology while 13 patients (19.1%) had malignancy. Superficial parotidectomy was alone in 48 patients (70.6%), total parotidectomy in 18 (26.5%) patients and extended parotidectomy was performed in 2 cases (2.9%). The most common post-operative complication was numbness of ear lobule (gradually improving with time) in 8 patients (11.8 %), followed by transient facial nerve paresis in 7 patients (10.3%). There was no hospital mortality.Conclusion: Parotid gland disorders affect each gender almost equally. Most of the patients present with benign pathology, superficial parotidectomy is the commonly offered surgical management. All parotid surgeries are safely performed in Department of ENT with minimum morbidity.TAJ 2018; 31(2): 21-26